Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Estimation of infectious dose and viral shedding rates for infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts - K Urquhart; A G Murray; A Gregory; M O’Dea; L A Munro; D A Smail; A M Shanks; R S Raynard (Journal of Fish Diseases, 2008)
Infectious dose and shedding rates are important parameters to estimate in order to understand the transmission of infectious pancreatic necrosis virus (IPNV). Bath challenge of Atlantic salmon post‐smolts was selected as the route of experimental infection as this mimics a major natural route of exposure to IPNV infection. Doses ranging from 10 2 to 10 −4 50% end‐point tissue culture infectious dose (TCID 50 ) mL −1 sea water were used to estimate the minimum infectious dose for a Scottish isolate of IPNV. The minimum dose required to induce infection in Atlantic salmon post‐smolts was −1 TCID 50 mL −1 by bath immersion (4 h at 10 °C). The peak shedding rate for IPNV following intraperitoneal challenge using post‐smolts was estimated to be 6.8 × 10 3 TCID 50 h −1 kg −1 and occurred 11 days post‐challenge. This information may be incorporated into mathematical models to increase the understanding of the dispersal of IPNV from marine salmon sites.

An evaluation of current diagnostic tests for the detection of infectious salmon anaemia virus (ISAV) following experimental water‐borne infection of Atlantic salmon, Salmo salar L. - M Snow; R S Raynard; A G Murray; D W Bruno; J A King; R Grant; I R Bricknell; N Bain; A Gregory (Journal of Fish Diseases, 2003)
Four commonly used diagnostic tests [reverse transcription polymerase chain reaction (RT‐PCR), indirect fluorescent antibody test (IFAT), virus culture and light microscopy] were evaluated for their ability to detect infectious salmon anaemia virus (ISAV) or tissue pathology following experimental infection of Atlantic salmon. Fish were infected with ISAV by water‐borne exposure which mimics the route of natural infection. Forty‐five per cent of pre‐clinical fish tested yielded positive results by RT‐PCR for at least one of the organs tested (kidney, heart, gill, liver, blood). No significant difference was detected between organs in the number or time of first occurrence of positive result. Virus culture identified a total of 14% of pre‐clinical fish as ISAV‐infected. The presence of ISAV in heart tissue was particularly notable (13% of fish sampled) as was the inability to culture virus from spleen tissue. In the case of IFAT, 15% of fish sampled were positive, although tissue other than kidney proved unsuitable for use in this method. Only limited ISAV‐specific pathology was detectable by histological examination of fish prior to the onset of clinical disease. These findings reveal important information regarding the optimal choice of both tissue sample and diagnostic test for the routine diagnosis of ISAV.

Studies on the use of hydrogen peroxide as a method for the control of sea lice on Atlantic salmon - D. W. Bruno; R. S. Raynard (Aquaculture International, 1994)